Effect of potassium silicate on epidemic components of powdery mildew on melon - Rodrigues, F. A.; Dallagnol, L. J.; Tanaka, F. A. O.; Amorim, L.pt-BR; Camargo, L. E. A. (Plant Pathology, 2011)
The effects of silicon (Si) supplied in the form of potassium silicate (PS) were evaluated on epidemic components of powdery mildew of melon under greenhouse conditions. The PS was applied to the roots or to leaves. In the first experiment, epidemic components were evaluated after inoculation with Podosphaera xanthii. In the second experiment, the disease progress rate was evaluated on plants subjected to natural infection. The area under the disease progress curve was reduced by 65% and 73% in the foliar and root treatments, respectively, compared to control plants, as a consequence of reductions in infection efficiency, colony expansion rate, colony area, conidial production and disease progress rate. However, root application of PS was more effective than foliar application in reducing most of the epidemic components, except for infection efficiency. This can be explained by the high Si concentration in leaf tissues with root application, in contrast to the foliar treatment where Si was only deposited on the external leaf surfaces. The effects of PS reported in this study demonstrated that powdery mildew of melon can be controlled, and that the best results can be achieved when PS is supplied to the roots.
Keywords: Cucumis melo; Epidemiology; Plant protection; Podosphaera xanthii; Silicon